Técnicas de RMN de Baixo Campo Aplicadas ao Estudo de Café e Propriedades Petrofísicas em Meios Porosos - Muniz, Rafael Oliari (2024)
This thesis reports the use of low-field nuclear magnetic resonance technique (LF-NMR) for the study of two works. The first work uses 1H LF-NMR relaxometry to detect concentrations in coffee samples of the Arabica and Robusta varieties. For this purpose, roasted and ground coffee samples from different Brazilian states' producing farms were used and categorized into two groups: pure samples (for both varieties) and blends (mixtures with different proportions of both varieties). As the method detects preferentially the NMR signals due to phases with high molecular mobility, which exhibit longer 2 values, the difference in the oil contents associated with Arabica and Robusta coffee was the key factor responsible for the detection of the contributions due to each variety. The calculations of relative hydrogen index (RHI) revealed a direct relationship between RHI values and the Arabica content in the blends; for the pure samples, higher RHI values were obtained for Arabica coffee samples from different origins, when compared to the values for all samples of the Robusta variety. The second work reports the use of a random walk-based algorithm to perform computational simulations reproducing experiments using the Carr-Purcell-Meiboom-Gill (CPMG) sequence. These simulations were applied to digital porous structures formed from the packing of interpenetrating spheres. Simulations are reported investigating the influences on magnetic relaxation curves of parameters such as porosity, relaxivity, temperature, Diffusion coefficient of the fluid filling the pore and magnetic susceptibility of the solid part of the rock. The results show that it is possible to capture, qualitatively, the main aspects observed in transverse magnetization relaxation experiments performed in porous media such as natural rocks. In particular, it is demonstrated that the presence of magnetic inhomogeneities is a decisive factor that must be considered when analyzing data regarding the temperature dependence of the relaxation rate.